A Hydrostable Cathode Material Based on the Layered P2@P3 Composite that Shows Redox Behavior for Copper in High‐Rate and Long‐Cycling Sodium‐Ion Batteries. (9th January 2019) - Yan, Zichao; Tang, Liang; Huang, Yangyang; Hua, Weibo; Wang, Yong; Liu, Rong; Gu, Qinfen; Indris, Sylvio; Chou, Shu‐Lei; Huang, Yunhui; Wu, Minghong; Dou, Shi‐Xue
Abstract: Low‐cost layered oxides free of Ni and Co are considered to be the most promising cathode materials for future sodium‐ion batteries. Biphasic Na0.78 Cu0.27 Zn0.06 Mn0.67 O2 obtained via superficial atomic‐scale P3 intergrowth with P2 phase induced by Zn doping, consisting of inexpensive transition metals, is a promising cathode for sodium‐ion batteries. The P3 phase as a covering layer in this composite shows not only in excellent electrochemical performance but also its tolerance to moisture. The results indicate that partial Zn substitutes can effectively control biphase formation for improving the structural/electrochemical stability as well as the ionic diffusion coefficient. Based on in situ synchrotron X‐ray diffraction coupled with electron‐energy‐loss spectroscopy, a possible Cu 2+/3+ redox reaction mechanism has now been revealed.